A historical review of the brazilian educational technology public policy - Sampaio, Robson B.; Amiel, Tel (Revista Hipótese, 2018)
In this study we provide a historical analysis of federal public policy focused on promoting technology in education in Brazil. We conducted a critical review that indicates that policy, beginning in the 1970’s, is part of a strategic vision of sovereignty and technological autonomy. This transforms itself, with much turbulence, into a policy which aims to reach the whole nation. We discuss many programs and actors involved in this process, putting emphasis on discontinuities. Even though many barriers existed, we identify elements that are long-lasting, such as the search for capillarity and decentralization and the notion of a federative agreement between different levels (municipality, states and federal government). In contrast, we highlight the implicit hierarchy established in most of these projects which demonstrate a centralizing role for the federal government. We also highlight the importance of public higher education institutions and research centers as disseminators of knowledge in this area.